MOTIVASI KOREA SELATAN MELAKUKAN INVESTASI BIDANG ENERGI MINYAK DI IRAN TAHUN 2016-2017 - Ihsan Fauzi Rahman; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The oil energy needs are very significant lately, making each state secure its petroleum energy needs. South Korea has a limited wealth of natural resources (especially petroleum). The South Korean government recognizes that oil is one of the dominant energies in driving the economy of South Korea. . One of the main forms of investment conducted by South Korea is investment in the oil energy field in Iran. The purpose of this study is to explain what the motivation of South Korea is investing in the oil energy field in Iran in the year 2016-2017.This research theoretically has built with liberalism perspectives on International Relations and supported by Foreign Direct Investment (FDI) theory. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems. Researcher has formulated answered-hypothesis whic reveals the fact that Motivation Of South Korea To Invest In Oil Energy Sector In Iran 2016-2017 is to create interdependence between South Korea and Iran in oil energy in order to supply and reserve South Korea Oil Is assured.Keywords :Motivation, Invest, Interest, Oil, Cooperation